INFLUENCE OF PRESSURE ON COAL FREEZING ADHESIVE STRENGTH - WANG ChunHua; XU HanWen; WANG ZhongXian; QU Hui (Jixie qiangdu, 2016)
Coal is the important basic energy in China,while the coal freezing adhesion seriously restricts with coal mine safe and efficient production in winter. Pressure as a secondary factor of coal freeze condition,it has an important influence on coal freezing adhesive strength. Through the freezing adhesive strength test device designed by ourselves,under conditions of- 25 ℃temperature and 3h freezing time,freezing adhesive characteristic of six different materials with moisture content 40% of the coal slime were tested. Studies have shown that pressure usually makes the coal freezing adhesive strength increase,such as Q235,normal freezing adhesive strength of under prepressure is 6. 2 times bigger than under no pressure’s,tangential freezing adhesive strength of under prepressure is 5. 9 times bigger than under no pressure’s. But only PTFE’s normal and tangential freezing adhesive strength under the condition of pressure both do not increase among six materials. In a sense,pressure will increase the hydrophilic material freezing adhesive strength,instead it will reduce the hydrophobic material freezing adhesive strength. The excellent characteristic of PTFE material shows wide application prospect in cold area of coal transportation,it deserves further study.